MODELING DIPLOMATIC STRATEGIES FOR SUSTAINABLE DEVELOPMENT IN THE CONTEXT OF GLOBAL TRADE - Korolchuk , L.; Savosh , L. (The actual problems of regional economy development, 2025)
The article examines the problem of optimizing diplomatic strategies in the field of sustainable development, taking into account the current challenges of global trade, in particular the need to balance economic interests, environmental safety and the requirements of international environmental standards. The study is aimed at analyzing economic and mathematical approaches to modeling the negotiation process, which allows assessing the effectiveness of various strategic decisions in the context of international interaction between countries with different levels of environmental adaptation. The methodological basis of the work is a combination of game theory and stochastic modeling implemented in the R environment, which makes it possible to conduct a numerical analysis of negotiation mechanisms using mathematical tools. In particular, a payoff matrix has been constructed that allows quantifying possible scenarios of the negotiation process and determining the equilibrium states of the system that ensure the optimal combination of economic and environmental interests of the participants. The scientific novelty of the study lies in the application of an integrated approach to the assessment of negotiation strategies in sustainable development diplomacy, combining stochastic modeling, game theory methods and analysis of the payoff matrix. The use of the Nash equilibrium analysis was further developed, which allowed not only to formalize the strategic interaction of the participants in the negotiation process, but also to assess the probability of choosing different strategies. The practical significance of the results obtained lies in the possibility of their application to optimize negotiation processes, formulate strategies for international cooperation and develop effective mechanisms for reconciling environmental obligations with the economic realities of states. The proposed approach can be used by governments, international organizations and financial institutions to assess the potential impact of environmental regulatory mechanisms, which will allow countries to adapt their trade policies to modern requirements, expand opportunities for cross-border cooperation and promote integration into sustainable economic models.